2020
DOI: 10.3168/jds.2019-17232
|View full text |Cite
|
Sign up to set email alerts
|

Symposium review: Comparisons of feed and milk nitrogen efficiency and carbon emissions in organic versus conventional dairy production systems

Abstract: Evaluation of feed efficiency (FE; calculated as energy-corrected milk yield/dry matter intake) and milk nitrogen efficiency (MNE; calculated as milk N yield/N intake) is needed to help farmers make decisions regarding the economic and environmental sustainability of dairy farms. Our primary objective was to compare FE and MNE data obtained from studies conducted with organic versus conventional dairy cows. Specifically, 3 data sets were constructed to meet this goal: (1) the organic Jersey data set (ORG-JE) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“… Hardie et al (2014) demonstrated via a cluster analysis using 69 organic-certified dairy farms from Wisconsin that dairies feeding the least amount of concentrate and relying heavily on pasture had lower milk rolling herd average (mean = 3,632 kg/cow per year) and income over feed costs ($5.76/lactating cow per d) than those with greatest concentrate and least reliance on grazed herbage (mean = 6,878 kg/cow per year of milk rolling herd average and $10.2/lactating cow per d of income over feed costs). However, organic grassfed milk markets can potentially counteract production losses due to additional premiums paid to farmers ( Benbrook et al, 2018 ; Brito and Silva, 2020 ; Snider et al, 2021 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Hardie et al (2014) demonstrated via a cluster analysis using 69 organic-certified dairy farms from Wisconsin that dairies feeding the least amount of concentrate and relying heavily on pasture had lower milk rolling herd average (mean = 3,632 kg/cow per year) and income over feed costs ($5.76/lactating cow per d) than those with greatest concentrate and least reliance on grazed herbage (mean = 6,878 kg/cow per year of milk rolling herd average and $10.2/lactating cow per d of income over feed costs). However, organic grassfed milk markets can potentially counteract production losses due to additional premiums paid to farmers ( Benbrook et al, 2018 ; Brito and Silva, 2020 ; Snider et al, 2021 )…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, consumers are willing to pay premiums for pasture-based milk and dairy products due to potential human-health benefits ( Benbrook et al, 2018 ; Stampa et al, 2020 ; Peira et al, 2020 ) and the perception that grazing is more environmentally friendly and welfare sounder than confinement ( Wong et al, 2010 ; Bir et al, 2020 ; Joubran et al, 2021 ). This opens opportunities to small dairies capitalize on organic certified and grassfed milk markets to remain economically viable ( Brito and Silva, 2020 ; Snider et al, 2021 ). However, only 10 to 15% of milk produced worldwide comes from grazing operations ( Shalloo et al, 2018 ) and, in Europe and Australia, inclusion of grazed herbage in dairy diets has been declining ( Hennessey et al, 2020 ; Joubran et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that Jersey cows, in organic systems, are less efficient than in conventional dairy systems by having 10.4% higher feed intakes, without a comparable increase in milk yield. However, these results were from a small meta-analysis dataset 38 . Although previous studies suggested Jersey genetics in organic and conventional low-input systems herds are likely to have lower milk output than HF cows 4 , this was not the case in the present study, where yield was not affected by crossbreeding.…”
Section: Discussionmentioning
confidence: 95%
“…Based on our previous research (Antaya et al, 2015(Antaya et al, , 2019, the concentration of I in ASCO meal averaged 774 mg/kg of DM. Using average values for DMI of 17.2 kg/d and BW of 427 kg in Jersey cows (Brito and Silva, 2020) and 5% inclusion of ASCO meal in diet DM (Belanche et al, 2016a;Zhou et al, 2018), intake of I would be 666 mg/d, which is about 10,000% greater than the 6.41 mg of I required daily by lactating cows (1.5 mg of I/100 kg of BW; NRC, 2001). Iodine toxicity (Olson et al, 1984) and enlargement of the thyroid gland (Ong et al, 2014) have been reported to occur with 500 mg/d of I intake and 7.5 to 12.5 mg of I intake/100 kg of BW in dairy cows, respectively.…”
Section: Introductionmentioning
confidence: 99%